Biocatalytic Photosynthesis with Water as an Electron Donor. Issue 38 (1st August 2014) - Ryu, Jungki; Nam, Dong Heon; Lee, Sahng Ha; Park, Chan Beum
Abstract Efficient harvesting of unlimited solar energy and its conversion into valuable chemicals is one of the ultimate goals of scientists. With the ever‐increasing concerns about sustainable growth and environmental issues, numerous efforts have been made to develop artificial photosynthetic process for the production of fuels and fine chemicals, thus mimicking natural photosynthesis. Despite the research progress made over the decades, the technology is still in its infancy because of the difficulties in kinetic coupling of whole photocatalytic cycles. Herein, we report a new type of artificial photosynthesis system that can avoid such problems by integrally coupling biocatalytic redox reactions with photocatalytic water splitting. We found that photocatalytic water splitting can be efficiently coupled with biocatalytic redox reactions by using tetracobalt polyoxometalate and Rh‐based organometallic compound as hole and electron scavengers, respectively, for photoexcited [Ru(bpy)3]2+. Based on these results, we could successfully photosynthesize a model chiral compound (L‐glutamate) using a model redox enzyme (glutamate dehydrogenase) upon in situ photoregeneration of cofactors.